2012
DOI: 10.1089/jmf.2011.1922
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature- and High Pressure-Processed Garlic Improves Lipid Profiles in Rats Fed High Cholesterol Diets

Abstract: Garlic protects against degenerative diseases such as hyperlipidemia and cardiovascular diseases. However, raw garlic has a strong pungency, which is unpleasant. In this study, we examined the effect of high temperature/ high pressure-processed garlic on plasma lipid profiles in rats. Sprague-Dawley rats were fed a normal control diet, a high cholesterol (0.5% cholesterol) diet (HCD) only, or a high cholesterol diet supplemented with 0.5% high temperature/high pressure-processed garlic (HCP) or raw garlic (HCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 19 publications
3
10
0
1
Order By: Relevance
“…In this study, the treatment with Ator drug showed significant increase in WBC in the test groups compared to the control. A significant depletion in serum HDL level was recorded in obese rats as compared to lean control rats, this result was in agreement with Sohn et al [62] who reported that hypercholesterolemia and hypertriglyceridemia have been previously detected in obese rats. The reduction in serum triglycerides leads to decreased adipose tissue mass [63,18].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the treatment with Ator drug showed significant increase in WBC in the test groups compared to the control. A significant depletion in serum HDL level was recorded in obese rats as compared to lean control rats, this result was in agreement with Sohn et al [62] who reported that hypercholesterolemia and hypertriglyceridemia have been previously detected in obese rats. The reduction in serum triglycerides leads to decreased adipose tissue mass [63,18].…”
Section: Discussionsupporting
confidence: 92%
“…We verified similar trends in the CGP group, fed with 13.52 mg of allicin/kg of animal mass, to the study conducted by Elkayam et al [24]. Other studies conducted by Lee et al [25] and Sohn et al [9], both with diets enriched with garlic powder, did not show any change in food intake and in weight gain.…”
Section: Cultivarssupporting
confidence: 91%
“…Atherosclerosis is one of the highest risk factor in hypertension development and CVD [9]. CVD are the main causes of death among the Western population.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of these previous studies believe that hypercholesterolemia should be considered as a risk factor for hepatic fibrosis, in addition to atherosclerosis and coronary artery disease 38 . Also shown in the study by Sohn CW was that the plasma TG level significantly increased after the feeding of high-cholesterol diets to rats 39 . Interestingly, our findings indicate no significant changes in the plasma TG but conspicuous steatosis and elevated triglycerides in the liver.…”
Section: Discussionmentioning
confidence: 87%